Retinopathy of prematurity: applicability of international and national screening guidelines in the north of Iran - Alizadeh, Yousef; Behboudi, Hassan; Dourandeesh, Maryam; Soltani-Moghadam, Reza; Akbari, Mitra; Medghalchi, Abdolreza; Azaripour, Ebrahim; Moravvej, Zahra (The Turkish Journal of Pediatrics, 2022)
Background. To determine the applicability of current international and national retinopathy of prematurity (ROP) screening guidelines and to identify a suitable community-based screening criterion. Methods. A retrospective study on premature neonates (≤37 weeks gestation) referred to a tertiary eye hospital ROP clinic in the north of Iran was conducted over a 10-year period. Neonates were classified as no ROP, with ROP and type 1 ROP. Data consisting of birth weight (BW), gestational age (GA) and chief risk factors were evaluated. Various screening criteria and currently established screening guidelines were applied and compared for applicability using a receiver operating characteristic curve. Results. A total of 716 neonates with a mean GA of 31.4 ± 2.8 weeks and BW of 1629 ± 502 grams were screened. The incidence of ROP was 22.9% and type 1 ROP requiring treatment was 0.28%. When applying the national Ministry of Health Guidelines, all neonates with type 1 ROP requiring treatment were identified; These criteria had a specificity of 7% for the diagnosis of type 1 ROP, and a large number of neonates (n=645) who are not at risk for type 1 ROP will be redundantly screened. Guidelines of the American Academy of Pediatrics and the UK would miss 4.5% of patients requiring ROP treatment. According to our data a threshold of GA≤32 weeks and/or BW ≤1600 grams demonstrated a sensitivity of 95.7% and specificity of 33.6% for the diagnosis of any ROP and a sensitivity of 100% and specificity of 26.8% for type 1 ROP requiring treatment. Conclusions. The ideal ROP screening guideline is one that is very sensitive and identifies patients requiring treatment without delay. To minimize redundant screening while maintaining optimum ROP requiring treatment diagnosis, we proposed a new local evidence-based screening guideline.